Peran Amaliyah Tadris dalam menumbuhkembangkan santri menjadi ustadz”: (Studi Kasus Di Pondok Pesantren Fajrul Karim) - Sayuti (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2022)
Pondok Pesantren Fajrul Karim is an educational, da'wah, and social institution that has a special program related to teaching practices that are selected with traditional amaliyah activities. This program is aimed at all students at the end of class XII as a form of realization of education and teaching in santri schools from class X to class XII at the Fajrul Karim Islamic Boarding School. It is hoped that the students will have the skills to enter the world of education and teaching, especially in the community in the future.This study aims to: (1) explain the background of tadris amaliyah activities at the Fajrul Karim Islamic Boarding School (2) describe and explain the implementation of tadris amaliyah activities at Fajrul Karim Islamic Boarding School (3) explain the role of tadris amaliyah in developing students to become teachers.This research includes field research using a qualitative approach. In collecting data, the writer uses interview, observation, and documentation methods as data collection techniquesFrom the results of the study, it can be said as follows: (1) The background of amaliyah activities at the Fajrul Karim Islamic Boarding School because tadris amaliyah activities are a compulsory curriculum for Islamic boarding schools, amaliyah activities are also held as a measurement of their understanding of learning material using Arabic and English as well as improving their mentality when they go into the community (2) the implementation of amaliyah generally consists of four stages, namely introduction (understanding of the concept of learning amaliyah adris) presentation of maddah (material), making i'dad (planning), teaching practice, evaluation (correction). As an exercise to practice what students have learned in theory from grade ten to grade twelfth as a debriefing material to become a teacher. (3) the role of amaliyah tadris, namely, to train students to display basic teaching skills, to train students to become good, creative, and fun teachers, as capital to go directly into the real field.